Investigating the relationship between reading comprehension and semantic skill in children with English as an Additional Language: a focus on idiom comprehension - McKendry, M (2014)
The current study builds upon previous UK EAL research by i. sampling EAL children who do not struggle with reading comprehension and ii. investigating participants’ semantic ability at the word, sentence and discourse levels. Four groups of 9-10 year old children were recruited: EAL Average Readers; EL1 Average Readers; EAL Above Average Readers; EL1 Above Average Readers. At the word level, EL1 participants significantly outperformed EAL participants on 2 out of 6 vocabulary measures administered (TOWK Expressive Vocabulary and Multiple Contexts). The results of an idiom comprehension measure (ICM) showed that EAL and EL1 participants did not differ in their ability to engage in semantic analysis or in inference from context (semantic ability at the sentence and at the discourse levels respectively). The EL1 Above Average group alone were able to use prior experience with English language idioms to their advantage when answering the ICM. For the EAL participants, relationships between performance on the TOWK Expressive Vocabulary and Multiple Contexts and on the ICM are stronger than for the EL1 participants. The relationships between performance on the ICM and on a measure of reading comprehension are also stronger for EAL than for EL1 participants. These results suggest the following: i. it is important to develop the vocabulary abilities of EAL children, as the relationships between word-level semantic skills and sentence/discourse level semantic skills are stronger for EAL children than for their EL1 peers; ii. the relationships between the knowledge and skills measured by the ICM (i.e. prior knowledge of English language idioms; semantic analysis; inference from context) and reading comprehension are stronger for EAL than for EL1 children, suggesting the importance of a comprehensive approach to the semantic development of EAL children.